Fungal Pathogenicity - Sultan, Sadia (IntechOpen, 2016)
This book is specially written for researchers at various levels, for example, in forestry, agriculture, industry, university and college laboratories. It describes the fungal pathogenicity; resistance behavior of fungal biofilms and its mechanisms; different categories of fungal infection and colonization patterns with example relevant to soybean; characteristics of white rob of corncob and head smut of maize such as cycle, pathogenicity factors, control methods, the abilities of chitosan and its derivatives to elicit resistance reactions in plants and its action in the production and viability of fungal spores; and the mode of actions of single constituents of different essential oils depending on different case studies. In addition, this book also describes the importance of synthetic peptides as an alternative tool for the diagnosis of cryptococcosis. Finally, a survey of fungal diseases occurring on trees of Namibia is described. This survey is the first dedicated step to find ways of protecting them from disease-causing agents.